Polycatechol-based iron predators disrupt fungal iron homeostasis to drive selective antifungal action - Nan Liu; Mingrui Cheng; Yuqi Tao; Xingchen Sun; Boyi Wu; Wenjing Ma; Xujiao Zhou; Jiaxu Hong; Jingjing Hu; Yiyun Cheng (Proceedings of the National Academy of Sciences, 2026)
Fungal infections pose a growing global health challenge, exacerbated by a scarcity of effective treatments and rising drug resistance. Although cationic polymers emerge as promising antifungal candidates owing to structural tunability, design flexibility, and resistance to proteolytic degradation, their clinical utility has been hampered by nonselective membrane-disruption mechanisms. Herein, we develop a class of polycatechols- termed fungal iron predators (FIPs), exhibit exceptional fungicidal activity and markedly low cytotoxicity. These FIPs can efficiently infiltrate fungal cells, selectively sequester labile iron, and disrupt iron homeostasis and metabolism. The ensuing iron starvation provokes severe mitochondrial dysfunction and energy collapse, culminating in fungal cell death. Through systemic optimization of cationic density and catechol stoichiometry, we obtained an FIP variant demonstrating potent antifungal activity with high selectivity toward fungi over mammalian cells, minimal propensity to induce resistance, and supplementary antioxidant properties. Remarkably, this FIP candidate shows robust therapeutic performance across multiple in vivo models of fungal infection. Critically, this work established a groundbreaking paradigm in polymer design: shifting the antifungal mechanism from traditional nonspecific membrane disruption to targeted intracellular metabolic interference. The general applicability of this strategy across diverse cationic polymer backbones opens avenues for developing next generation of precision antifungal agents.